Local communities on-line: mapping local Web-TVs in Italy - Giacomo Andreucci (Netcom)
A wider spreading of broadband in Italy in recent years has led to the birth of many web-TVs originating from a variety of actors (educational institutions, public administrations, informal groups, etc.). A specific role is being played by local communities (neighborhoods, social centers, parishes, etc.) which, thanks to the on-line spreading of video content, can have their own TV channel to reach their members and promote themselves in global networks. This essay will map the distribution of these locally-originated web TVs in Italy investigating their ways of strengthening communication within the community and at the wider level of the global Internet network.